PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS XII MIPA SMAN 8 PADANG - Yorend, Yollanda; Jamaan, Elita Zusti (Departemen Matematika, 2024)
Student achievement at the end of the learning process is called learning outcomes. Students in grade XI MIPA at SMAN 8 Padang recorded below-standard learning outcomes in mathematics. Passive learning is one of the causes. One alternative that can be applied is cooperative learning, namely the Student Teams Achievement Division (STAD) model. This study used a posttest-only non-equivalent control group design with a quasi-experimental approach. Data analysis and hypothesis testing proved that students taught using STAD-type cooperative learning were better than students taught using traditional methods.Keywords – STAD, Learning Outcomes, Conventiona